Numerical Investigation of the Wing-in-Ground Effect on Aerodynamic Characteristics - Maciej MAJCHER (Numeryczne badania wpływu efektu przypowierzchniowego na charakterystyki aerodynamiczne, 2016)
This paper presents the numerical evaluation of ground (proximity) effects on the basic aerodynamic characteristics of a specifically designed airplane model. The ground effects were investigated in relation to the angle of attack and flight altitude. The results were referenced to the characteristics of an object in motion unaffected by ground effects.
Keywords: Wpływ efektu przypowierzchniowego